(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Gingival displacement is a crucial procedure in fixed prosthodontics, ensuring clear visualization of subgingival margins during impression-making. This cross-sectional study aimed to assess the knowledge, attitude, and practice (KAP) of gingival displacement techniques among postgraduate dental students in India. A structured questionnaire was circulated among prosthodontic postgraduates between January and March 2025, receiving 160 valid responses. The survey investigated awareness of retraction materials, clinical application patterns, and procedural preferences. The results revealed that 77% of students routinely used retraction cords, while none reported consistent use of retraction pastes in clinical practice. Additionally, 76.7% used hemostatic agents alongside cords, with aluminium chloride being the most cited. However, only 26.2% reported using gingival curettage (gingitage), and 24.4% employed electrosurgical methods. Although the majority exhibited strong theoretical knowledge and positive attitudes, a significant gap was observed in diversified clinical practices. These findings suggest a need to harmonize postgraduate clinical training across institutions, with greater emphasis on practical exposure to multiple displacement techniques. Future curricula may incorporate simulation-based training and emphasize evidence-based selection of gingival management tools. This study serves as a baseline for assessing prosthodontic protocols at the postgraduate level in India